PERANCANGAN LANSKAP TAMAN TEMATIK AROMATERAPI KEBUN RAYA KUNINGAN JAWA BARAT - Wardiman Malik Sahabudin; Diah Ivoniarty (University of Insan Cendekia Mandiri, 2019)
The Aromatherapy Garden of Kuningan Botanical Garden (KRK) is an effort to fulfill the need for recreation area in Kuningan Regency based on ecological and aesthetic value. The location of the design is in the middle of KRK, KRK location is in Padabeunghar Village, Pasawahan District, Kuningan Regency, West Java Province and directly adjacent to Gunung Ciremai National Park. The design area is 6.6 hectares divided into 4.7 hectares of land and 1.9 hectares of water (Situ Cibuntu). Thematic garden landscape design The Aromatherapy of Kuningan Botanical Garden is a continuity process that starts from the survey, analysis, synthesis and concept stages into the drawings in the form of floor plans, looks, pieces and complete details and specifications and material selection. Aromatherapy Park is a garden whose plant composition is dominated by various types of plants that can spread the scent of flowers, leaves, stems, roots, fruit and extract from the plant itself. This garden can be a therapeutic garden (healing garden), because aromatherapy plant can give the impression of relaxation and fresh. Through Aromatherapy Park visitors are invited to relax to forget for a moment the pain, releasing stress and physical fatigue caused by everyday activities. The aroma that is generated from various types of plants is expected to motivate the psychic to be more relaxed, calm and feel a freedom so it can affect the physical to achieve progress